Sorsfordító levelek az Özvegy és leányában - Pintér, Borbála (Studia Litteraria, 2014)
It’s been a quarter of a century since the rereading of Zsigmond Kemény’s oeuvre began. By now, the reception of Kemény is open to modern trends and has become a decisive tradition in the history of reception. Following this tradition, I prepared my talk for the bicentennial conference discussing Kemény’s novel The Widow and Her Daughter. My approach uses a reading open to romantic form principle; however, it is also a deviation from it with special regards to the schemes of intertextuality, composition, language and self-reflection while paying special attention to the act of reception and meaning attribution. In my essay I scrutinize letters shaping the texture of the novel. The special focus on the letters obviously emphasizes certain tendencies of interpretation. In my analysis I follow an approach of interpreting insertions into the main body text as structural inserts, while attributing decisive role to letter inserts in the narrative structure of Kemény’s novels. I attempt to analyze letters inserted into The Widow and Her Daughter from a textological and typological point of view, paying special attention to the dynamic aspect in the organization of the novel’s plot. The genre itself offers great opportunity to focus on the matter of fact concreteness of letter; which, as a consequence, can function – as we shall see – a rather mere intradiegetic narrative structure; furthermore, as an organizing principle of the plot through repetition, copying, violation of the sanctity of mail, the attachment etc.